Weakly-Supervised Semantic Segmentation via Sub-Category Exploration - Chang, Yu-Ting; Wang, Qiaosong; Hung, Wei-Chih; Piramuthu, Robinson; Tsai, Yi-Hsuan; Yang, Ming-Hsuan (Proceedings (IEEE Computer Society Conference on Computer Vision and Pattern Recognition. Online), 2020)
Existing weakly-supervised semantic segmentation methods using image-level annotations typically rely on initial responses to locate object regions. However, such response maps generated by the classification network usually focus on discriminative object parts, due to the fact that the network does not need the entire object for optimizing the objective function. To enforce the network to pay attention to other parts of an object, we propose a simple yet effective approach that introduces a self-supervised task by exploiting the sub-category information. Specifically, we perform clustering on image features to generate pseudo sub-categories labels within each annotated parent class, and construct a sub-category objective to assign the network to a more challenging task. By iteratively clustering image features, the training process does not limit itself to the most discriminative object parts, hence improving the quality of the response maps. We conduct extensive analysis to validate the proposed method and show that our approach performs favorably against the state-of-the-art approaches.